The Effect of Hospital Service Quality, Perceived Value, and Perceived Price on Patient Loyalty and Patient Satisfaction - Jannah, Weni Miftachul (Almana : Jurnal Manajemen dan Bisnis, 2025)
Public health centers play a strategic role in shaping positive patient experiences that influence satisfaction and loyalty. This study aims to analyze the influence of service quality, perceived value, and perceived price on patient satisfaction and loyalty. Using a quantitative explanatory approach, data were collected from 397 respondents selected through purposive sampling from the 2023 patient population. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that service quality and perceived value have a positive and significant effect on patient satisfaction, while perceived price has a moderate influence. Patient satisfaction significantly mediates the relationship between the three independent variables and patient loyalty. These findings highlight the importance of improving service quality and enhancing perceptions of value and pricing to create a satisfying healthcare experience and foster long-term loyalty. The study provides practical insights for healthcare managers to strengthen service delivery and offer transparent pricing information, as well as empirical evidence for developing strategies to improve primary healthcare services based on patient satisfaction and loyalty.